AN ANALYSIS OF ONOMATOPOEIA TRANSLATION IN "THE LIFE AND TIMES OF SCROOGE MC DUCK" COMIC BOOK :A CASE STUDY OF THE ENGLISH-INDONESIAN TRANSLATION OF ONOMATOPOEIA - Angelina Citra Sari, - (2008)
This study was investigating translators' translation procedures, problems and solutions in translating onomatopoeia in "The Life and Times of Scrooge Mc Duck" comic book. The study involved two well-known Indonesian translators of novel and comic. A qualitative approach, particularly case study, was employed in this study. The data were collected through translation test and interviews were conducted with the translators via e-mail and on-line chat. The data from the translators' translation were analyzed by using the translation procedures theory proposed by Newmark (1988). Meanwhile, the data from interviews were analyzed to discuss the problems encountered by the translators in translating the task and also the solutions they used in handling the problems. The study revealed that the translators employed four procedures of translation from Newmark (1988) to translate onomatopoeic words that are transference, naturalization and cultural equivalent. Cultural equivalent is the mostly used procedure. The linguistic problems encountered by the translators were mostly about lexical and semantic ambiguities. They handled those problems mostly by interpreting the SL word to the TL word that has relevant equivalent meaning. The multicultural languages in Indonesia cause the cultural problem in translating the onomatopoeic word, since different languages may contain different cultures or different ways of thinking. To overcome the problem, the translators use the TL that most frequently used in Indonesia based on her sense of personal.